2016
DOI: 10.1021/acsmacrolett.6b00178
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Poly(ionic liquid)s: Synthesis and Application as Quasi-Homogeneous Catalysts in the Reaction of Ethylene Carbonate with Aniline

Abstract: Homogeneous catalysts generally show higher catalytic activities, while heterogeneous catalysts are more easily separated from products. To combine the advantages of heterogeneous and homogeneous catalysts has been of great interest for many years. Here, we report a kind of facilely prepared cross-linked poly­(ionic liquid)­s (PILs) with swelling property to increase catalytic activities of heterogeneous catalysts. The swelling ability of PILs was greatly affected by cross-linking density and chain length of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 40 publications
1
65
0
Order By: Relevance
“…Therefore, these swollen polymers could be considered as PIL‐based organogels and might provide a suitable microenvironment with enhanced catalytic performance during the chemical transformation of CO 2 . Similar inferences and interesting phenomena have also been reported by Gao et al., Ding et al., and others…”
Section: Resultssupporting
confidence: 91%
“…Therefore, these swollen polymers could be considered as PIL‐based organogels and might provide a suitable microenvironment with enhanced catalytic performance during the chemical transformation of CO 2 . Similar inferences and interesting phenomena have also been reported by Gao et al., Ding et al., and others…”
Section: Resultssupporting
confidence: 91%
“…Notably, P[VBIM][OAc]‐10% exhibited an even better catalytic performance than homogeneous catalyst BmimOAc (87%) (entry 8). This implied that the swelling ratio of PILs had a great influence on their catalytic activities . With same number of active sites, the PILs with higher swelling ratio exhibited higher activities mainly due to the sufficient exposure of active sites to reactants.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of anion decreased in order OAc − > Cl − ≈ Br − , which was in agreement with hydrogen bond basicity according to our previous reports,. P[VBIM][AA]‐10%, where the carboxylate group was connected to the polymer chain, gave a relatively lower yield (82%) than P[VBIM][OAc]‐10% (95%) (entry 7). This suggested that the mobility of catalytically active sites also played an important role in the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations